Komunikasi Negosiasi Dalam Perspektif Islam - Lulus Setiawan, Wawan; Harmonis, Harmonis (Universitas Koperasi Indonesia, 2024)
Communication is an important element in human life. Every human being is bound to communicate either verbally or non-verbally. However, today's society does not ignore the principles that need to be adhered to when communication takes place. Negotiation is used to bridge different interests, between producers and consumers. Business ethics are important in this era of increasingly fierce business competition. The many cases of violations in the business world that have caused adverse impacts on each other, this raises the importance of business ethics awareness. Doing business in the era of disruption requires Islamic Business Ethics in order to achieve business profits without destroying each other. Islam teaches to be honest, trustworthy and fair in doing business and to avoid manipulation, harm, speculation, monopoly and hoarding, and usury. Islam provides a boundary or dividing line between what is allowed and what is not allowed, what is right and wrong and what is halal and haram.